2015
DOI: 10.1055/s-0035-1563696
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Treatment of Pubertal Delay in Duchenne Muscular Dystrophy

Abstract: A broad range of testosterone preparations was used. Testosterone was generally well-liked, but side effects were experienced by some patients and the pubertal growth increment appears to be compromised. Few subjects had adult endogenous testosterone levels posttreatment. Controlled studies are required to determine the most appropriate treatment regimen and the precise impact of testosterone on key outcomes, such as muscle function and bone integrity. Clinicians will then be better placed to advise families a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…The increase in BMD LS could not be solely explained by very small increases in height, far less than the 25-cm height increase over puberty that is seen in healthy boys and less than that previously reported in a small cohort of boys with DMD treated briefly with testosterone for pubertal delay [21]. The majority accrual of bone mass of our cohort is thus due to testosterone effect.…”
Section: Discussion/conclusioncontrasting
confidence: 72%
“…The increase in BMD LS could not be solely explained by very small increases in height, far less than the 25-cm height increase over puberty that is seen in healthy boys and less than that previously reported in a small cohort of boys with DMD treated briefly with testosterone for pubertal delay [21]. The majority accrual of bone mass of our cohort is thus due to testosterone effect.…”
Section: Discussion/conclusioncontrasting
confidence: 72%
“…A recent retrospective review found that testosterone was generally well tolerated and perceived to be beneficial by individuals with DMD and their families. 103 …”
Section: Endocrine Managementmentioning
confidence: 99%
“…It is possible that some boys with DMD have a contiguous gene deletion which may be associated with hypogonadotrophic hypogonadism. Thus, in contrast, in boys with DMD, testosterone therapy is commenced and gradually increased until adult replacement dose is attained over a period of 2-3 years, evaluating for testicular growth during treatment indicating endogenous gonadotrophin activity [72]. …”
Section: A Proposed Pathway Of Clinical Monitoring Of Bone Health Andmentioning
confidence: 99%